QUANTIFICATION OF VARIOUS ISOFLAVONES EXTRACTED FROM RED CLOVER (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article describes methods of new ecological extraction of isoflavonoids fromred clover flowers based on the use of deep eutectic solvents (NADES), consisting of citric acidand choline chloride are described, with simultaneous extraction of associated biologically activecompounds. Data are given on. An analysis of the total polyphenols and antioxidants, includingisoflavones, showed that NADES with a 30% water concentration was the most effective forextraction.
Keywords: plant material, phytoestrogens, isoflavonoids, extraction methods, extract of red clover flowers.